KARAKTERISTIK STOMATA DAN BENTUK-BENTUK AKTIVITAS PEMANFAATAN MANGROVE SEBAGAI DASAR PENGELOLAAN EKOSISTEM MANGROVE DI PERAIRAN DESA WAIHERU DAN DESA LEAHARI - Simatauw, Annielisye; Tupan, Charlotha I; Mamesah, Juliaeta A B (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2024)
Mangrove stomata play an important role in the process of photosynthesis and transpiration. Environmental pressure on mangrove forests results in a decrease in the function and important role of mangrove stomata for the environment. The purpose of this study was to analyze the density, number, type and distribution of mangrove leaf stomata; analyze the effect of temperature, salinity, pH, DO and light intensity parameters on the density, number of types and distribution of stomata; identify forms of mangrove ecosystem utilization activities; and formulate mangrove ecosystem management strategies in the waters of Waiheru Village and Leahari Village. This research took place in February-May 2024 in the waters of Waiheru Village and Leahari Village. The methods used were observation and interview methods. Mangrove leaves were analyzed at the Pattimura University Masela Block Support Integrated Laboratory, while the forms of use and management directions were analyzed descriptively qualitatively. The results showed that the stomatal density of the three species was in the high category. Anomocytic stomata type and scattered stomata distribution in the three species. Water parameters in the waters of Waiheru Village and Leahari Village are 31℃ and 32℃ for temperature, 20‰ and 21‰ for salinity, 8.3 and 8.1 for pH, 1.88 and 6.07 mg/l for DO. Water quality parameters affect stomatal density but not the pH parameter. Community activities in Waiheru Village were identified in the form of building tourist attractions, selling mangrove seedlings, mooring boats, marine fish farming and fishing. Activities in Leahari Village include mooring boats, bameti and fishing. Formulated 8 directions for mangrove ecosystem management in Waiheru Village, and 6 directions for mangrove ecosystem management in Leahari Village. ABSTRAK Stomata mangrove berperan penting dalam proses fotosintesis dan transpirasi. Tekanan lingkungan terhadap hutan mangrove mengakibatkan penurunan fungsi dan peran penting stomata mangrove bagi lingkungan. Tujuan dari penelitian ini untuk menganalisis kerapatan, jumlah, tipe dan distribusi stomata daun mangrove; menganalisis pengaruh parameter suhu, salinitas, pH, DO dan intensitas cahaya terhadap kerapatan, jumlah tipe dan distribusi stomata; mengidentifikasi bentuk-bentuk aktivitas pemanfaatan ekosistem mangrove; dan merumuskan strategi pengelolaan ekosistem mangrove di Perairan Desa Waiheru dan Desa Leahari. Penelitian ini berlangsung pada Februari-Mei 2024 di perairan Desa Waiheru dan Desa Leahari. Metode yang digunakan adalah metode observasi dan wawancara. Daun mangrove dianalisa di Laboratoriuim Terpadu Pendukung Blok Masela Universitas Pattimura, sedangkan bentuk-bentuk pemanfaatan dan arahan pengelolaan dianalisa secara deskriptif kualitiatif. Hasil penelitian menunjukkan kerapatan stomata ketiga spesies termasuk dalam kategori tinggi. Tipe stomata anomositik dan distribusi stomata yang tersebar pada ketiga spesies. Parameter perairan di Perairan Desa Waiheru dan Desa Leahari masing-masing yaitu untuk suhu 31 dan 32 , nilai salinitas 20‰ dan 21‰, nilai pH 8,3 dan 8,1, nilai DO 1,88 dan 6,07 mg/l. Parameter kualitas perairan mempengaruhi kerapatan stomata namun tidak untuk parameter pH. Teridentifikasi aktivitas masyarakat di Desa Waiheru berupa membangun tempat wisata, menjual bibit mangrove, menambat perahu, budidaya ikan laut dan penangkapan ikan. Aktivitas di Desa Leahari berupa menambat perahu, bameti dan penangkapan ikan. Dirumuskan 8 arahan pengelolaan ekosistem mangrove di Desa Waiheru, dan 6 arahan pengelolaan ekosistem mangrove di Desa Leahari. Kata Kunci: Stomata, mangrove, pemanfaatan, Desa Waiheru, Desa Leahari